BI-HYPERIDEALS AND QUASI-HYPERIDEALS IN ORDERED SEMIHYPERGROUPS - Changphas, Thawhat; Davvaz, Bijan (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we introduce concepts of bi-hyperideals and quasi-hyperideals of an ordered semihypergroup and present several examples of them. Some properties and relationships between bi-hyperideals and quasi-hyperideals are investigated. In particular, we introduce the concept of intra-regular ordered semihypergroups and give their characterizations in terms of bi-hyperideals and quasi-hyperideals.